(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of experiments on the use of water-saving technologies when growing the cotton variety Bukhara-8 in conditions of saline soils in 4 variants, in scientific studies it was established that in scientific studies in the first irrigated variant the irrigation rate is 892-1162 cbm/ha and the seasonal irrigation rate is 5119 cbm/ha with a cotton yield of 3.55 t/ha. In the second option with drip irrigation, cotton had an irrigation rate of 224-342 cbm/ha and a seasonal irrigation rate of 3796 cbm/ha with a yield of 4.62 t/ha. Also in the third option, where the black film bed was irrigated when growing cotton, the seasonal irrigation rate was 3603 cbm/ha, the cotton yield was 4.41 t/ha. In the fourth option, where during the experiments the introduction of a hydrogel organic compound into the soil when growing cotton was supported, the irrigation rates were 714-966 cbm/ha, and the seasonal irrigation rate was 4381 cbm/ha, while the cotton yield in this option was 4.21 t/ha.